Decreased risk of renal impairment in atrial fibrillation patients receiving non-vitamin K antagonist oral anticoagulants: A pooled analysis of randomized controlled trials and real-world studies. Issue 174 (February 2019) - Zhang, Chi; Gu, Zhi-Chun; Ding, Zheng; Shen, Long; Pan, Mang-Mang; Zheng, Ying-Li; Lin, Hou-Wen; Pu, Jun
Abstract: Background: Patients with warfarin have a potential risk of warfarin-related nephropathy, which could result in the discontinuation of anticoagulation therapy. The question of whether non-vitamin K antagonist oral anticoagulants (NOACs) use is associated with increased risk of renal impairment in atrial fibrillation (AF) patients remains unanswered. Methods: Studies were systematically searched through Medline, Embase, Cochrane Library databases, andClinicalTrials.gov Website. Randomized controlled trials (RCTs) reporting renal impairment events and observational nationwide database studies presenting adjusted hazard ratio (HR) in AF patients with NOACs were identified. The Primacy outcome was renal impairment, defined as a composite of any renal disorder. The secondary outcomes were narrow definition of renal failure (including renal failure, acute renal failure, chronic renal failure, acute prerenal failure and postrenal failure) and individual renal impairment reported in involved studies. HR and 95% confidence intervals (95%CI) were calculated using fixed- or random-effects models according to the extent of heterogeneity. Subgroup analyses were conducted according to individual NOACs, study types and different controls. Results: Totally, 189, 483 patients from 11 RCTs and 3 observational database studies were included in the analysis (119, 188 patients with NOACs and 70, 295 patients with vitamin K Antagonists or acetylsalicylic acid). Overall results indicated a significantly lower risk of renal impairment in AF patients with NOACs versus VKAs/acetylsalicylic acid (HR: 0.67, 95%CI: 0.62–0.73). Results of narrow definition of renal impairment were accordant with the primacy outcome (HR: 0.65, 95%CI: 0.60–0.71). Compared with VKAs or acetylsalicylic acid, dabigatran (HR: 0.64, 95%CI: 0.56–0.72), rivaroxaban (HR: 0.66, 95%CI: 0.55–0.77) and apixaban (HR: 0.73, 95%CI: 0.59–0.87) were all associated with a significantly lower risk of renal impairment, with the exception of edoxaban (HR: 0.79, 95%CI: 0.30–1.27). Conclusions: Patients with NOACs might bring about a lower risk of renal impairment compared to VKA or acetylsalicylic acid. Further specialized designs of RCTs and real-world studies on evaluation of renal function are warranted to obtain a robust result on this issue. Highlights: Anticoagulant-related nephropathy could result in the discontinuation of anticoagulation therapy. High-quality observational studies can provide more valuable information on identifying additional risk of novel agents. The use of NOACs might confer a lower risk of renal impairment compared with VKA or acetylsalicylic acid in AF patients.